Health Care in the Age of Mass Incarceration: A Selective Course for Medical Students in Their Preclinical Years - Julia Gips; Alina Spiegel; Alexandra Norton; Priyal Gandhi; Dylan Hardenbergh; John Gatti; Laura Pugh; Amanda Jones; Carolyn Sufrin (Association of American Medical Colleges, 2020)
Introduction While medical school curricula increasingly address health disparities, content regarding health care for persons impacted by incarceration is a persistent and notable gap. There is a high burden of disease among incarcerated populations, and health care challenges continue postincarceration. We developed a course to introduce medical students to the current landscape of mass incarceration in the US and implications for health and health care delivery to people impacted by this system. Methods We developed a 3.5-hour elective course taken by 19 first-year medical students in its first year and 20 students in its second. The course utilized lecture, case-based discussion, and guest speaker modalities to introduce students to the history of mass incarceration, health care delivery within the carceral system, and challenges in accessing care during and following incarceration. Results Students received two surveys after completing the course. In the first, 100% of respondents reported outstanding, excellent, or good levels of satisfaction with various elective components, including organization, learning activities, and student discussion. The second found significant increases in knowledge about mass incarceration and incarceration health issues, in addition to significant increases in interest in advocating or providing health care for incarcerated populations. Discussion Given current mass incarceration practices, students will encounter patients impacted by this system. This elective course sought to better prepare students to effectively care for these patients. We were limited by time availability, and future directions include incorporating a standardized patient exercise, trauma-informed care principles, and providers working within the carceral system.